Enhancing Search Result Delivery Using Web Content Mining and Web Usage Mining (International Journal of Scientific Research and Management (IJSRM), 2014)
In today’s e-world search engines play a vital role in retrieving and organizing relevant data for various purposes. However, in the real ground relevance of results produced by search engines are still debatable because it returns enormous amount of irrelevant and redundant results. Providing relevant information to user is the primary goal of the website owner. Web mining is ample and powerful research area in which retrieval of relevant information from the web resources in a faster and better manner. Web content mining improves the searching process and provides relevant information by eliminating the redundant and irrelevant contents. However for a broad-topic and ambiguous query, different users may have different search goals when they submit it to a search engine. Web usage mining plays an important role in inferring user search goals as they can be very useful in improving search engine relevance and user experience. The paper focuses on combine approach of web usage mining and web content mining.